Development of Mental Health Indicators in Iran - khosro mohamadi; Khodabakhsh Ahmadi; Ali Fathi Ashtiani; parviz Azad Fallah; Abbas Ebadi (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Promoting mental health and preventing mental health problems are important tasks for directors, officers and mental health professionals. This objective requires the establishment of information networks and systems enable efficient data collection and determining indicators of mental health. This study was conducted to determine the mental health Indicators in Iran. Methods: This study was performed based on Q methodology in six stages: 1) development of Q sample statements, 2) selection of participants (professionals in health and mental health) for the Q sort, 3) Q-sorting, 4) data entry, 5) statistical analysis (for the extraction of Q sorts, the principal components analysis method was used), and 6. factor interpretation. Results: Twenty-one indicators were offered in three categories: mental health status, mental health service and mental health system. Conclusion: This study was a preliminary study for iden‌tification of mental health indices that reflects the status of mental health in Iran. Indicators obtained in this study can also be used in regulatory reforms and policies, providing appropriate mental health services, mental health promotion, updates and measuring mental health information.